The effect of a primary school multi-media package and instruction on conceptual change in pre-service teachers - Mahapa, Sekgobokoane Shadrack (My University, 1995)
This project is concerned with a multimedia package which incorporates comics, video and pupil workbooks. The intention as to determine the effectiveness of the package on the conceptual change of pre-service teachers, using an empirical research method and decriptive analysis of results. Logistical constraints experienced at colleges of education and schools led to an alternative evaluation of the packaqe with D.E.T. college lecturers at RADMASTE workshop. Results indicated that, if properly administered, the multimedia package can assist users in identifying and changing tneir interfering preconceptions and misconceptions while they are enjoying the story.
A research report in partial fulfilment of the requirements for the degree of Master of Science in the School of Science Education of the Witwatersrand. Johannesburg, 1995.
Keywords: Science--Study and teaching (Elementary)--South Africa--Audio-visual aids; Science teachers--In-service training--South Africa.